PUZZLE-BASED LEARNING TO ENHANCE BODY PARTS KNOWLEDGE IN SECOND-GRADE STUDENTS WITH INTELLECTUAL DISABILITIES AT SLB NEGERI KARANGANYAR - Muhammad Hamdany Munawwa; Munawir Yusuf; Dewi Sri Rejeki (Journal of Disability, 2024)
Special schools are educational institutions specifically designed for students with intellectual disabilities. Students with intellectual disabilities are often referred to as children with special needs who experience limitations in their cognitive abilities ranging from mild to severe. This study aims to determine whether puzzle-based learning can enhance knowledge about body parts in second-grade mentally disabled children at SLB Negeri Karanganyar. The research approach used is quantitative saturation sampling. Data collection for the research used a written test instrument with a total of 11 multiple-choice questions. The data analysis technique used to test the research hypothesis is the Wilcoxon Sign Rank Test. The results of this study show an increase in students' scores from 56.67 in the pretest to 83.33 in the posttest. The conclusion of this study is that puzzle-based learning games have an impact on improving knowledge about body parts for second-grade students with intellectual disabilities at SLB Negeri Karanganyar.